Systemic Risk in Banking, Fire Sales, and Macroeconomic Disasters - Spiros Bougheas; David I. Harvey; Alan Kirman; Douglas Nelson (Center for Economic Studies and ifo Institute (CESifo), 2024)
We develop a dynamic computational network model of the banking system where fire sales provide the amplification mechanism of financial shocks. Each period a finite number of banks offers a large, but finite, number of loans to households. Banks with excess liquidity also offer loans to other banks with insufficient liquidity. Thus, each period an interbank loan market is endogenously formed. Bank assets are hit by idiosyncratic shocks drawn from a thin tailed distribution. The uneven distribution of shocks across banks implies that each period there are banks that become insolvent. If insolvent banks happen also to be heavily indebted to other banks, their liquidation can trigger other bank failures. We find that the distribution across time of the growth rate of banking assets has a 'fat left tail' that corresponds to rare economic disasters. We also find that the distribution of initial shocks is not a perfect predictor of economic activity; that is some of the uncertainty is endogenous and related to the structure of the interbank network.
Keywords: E44; G01; G21; 330; systemic risk; fire sales; banking network; macroeconomic shocks